Bio-Surfactant assisted room temperature synthesis of cubic Ag/RGO nanocomposite for enhanced photoreduction of Cr (VI) and antibacterial activity. Issue 2 (April 2021) - Devi, Aparna Prabha; Padhi, Deepak Kumar; Mishra, Pravat Manjari; Behera, Ajay Kumar
Graphical abstract: Room temperature assisted eco-friendly in-situ fabrication of cubic Ag nanoparticles over RGO sheets for photoreduction of Cr (VI) under visible light irradiation and its antibacterial activity. Highlights: Room temperature assisted in-situ synthesis of cubic AgNPs on RGO sheets using leaf extract as green reducing agent. At pH 2, 5 wt% of AgNP loaded RGO cubic nanocomposite shows 99.7 % Cr(VI) reduction under visible light irradiation. The presence of ethanol as hole-scavenger escalated Cr (VI) reduction over Ag/RGO followed by zero order kinetics. Excellent antibacterial activity against various human pathogens. Abstract: We report a unique, environment friendly, and one-pot synthesis of cubic Ag nanoparticles (AgNPs) fabricated on reduced graphene oxide sheets (RGO) in presence of Averrhoa carambola leaf extract as a green reducing and stabilizing agent without using any toxic and expensive chemicals. The polyphenolic groups present in the leaf extract reduced both AgNO3 and graphene oxide at room temperature to obtain cubic like morphology of AgNPs over RGO. Structural characterizations such as XRD, Raman, XPS, DRUV-Vis, FTIR, FESEM, TEM, HAADF-STEM, and PL analysis were performed. Several batch experiments were implemented to investigate the photocatalytic activity of Ag/RGO, in comparison to both chemically and green synthesized AgNPs under visible light irradiation. In presence of ethanol as hole scavenger, 5 wt% cubic AgNPs loaded on RGO showed 99.7 % Cr (VI) reduction. 5Ag/RGO photocatalyst can be reused up to 4 cycles without any remarkable loss. The reaction kinetics was best described by zero order rate equation for all the nanocomposites. In addition, 5Ag/RGO exhibited potential antibacterial activity against two Gram-positive and one Gram-negative pathogens as compared to GO.